ZnSSe-C composite material with hollow multi-shell structure as well as preparation method and application of ZnSe-C composite material

By preparing a hollow multi-shell ZnSSe@C composite material, the problems of volume change and conductivity of sodium-ion battery anode materials were solved, improving the electrochemical performance and cycle stability of the battery, and making it particularly suitable for sodium-ion battery anode materials.

CN120933354AActive Publication Date: 2025-11-11ZHEJIANG SCI-TECH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511470095.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-15
Publication Date
2025-11-11
Estimated Expiration
2045-10-15

AI Technical Summary

Technical Problem

Existing zinc sulfide anode materials for sodium-ion batteries suffer from large volume changes, low conductivity, and slow kinetics during electrochemical reversible processes, which affect their electrochemical performance.

Method used

By preparing hollow multi-shell ZnSSe@C composite materials, phenolic resin was used as a template to control the material size, and selenium was doped into zinc sulfide to construct a multi-shell structure to enhance electronic conductivity and adapt to volume changes.

Benefits of technology

It improves the electrochemical performance of sodium-ion batteries, enhances cycle stability and reversible capacity, provides a larger specific surface area and reaction interface, and improves the energy density and rate performance of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120933354A_ABST
    Figure CN120933354A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new-generation energy materials, in particular to a ZnSSe-C composite material of a hollow multi-shell structure and a preparation method and application of the ZnSSe-C composite material. The preparation method is characterized by comprising the following steps: firstly preparing phenolic resin microspheres which are consistent in size and are uniformly dispersed as a template, then carrying out water bath and gas phase sintering to obtain a ZnSSe (at) C spherical composite material which is uniformly dispersed in size, and finally, controlling the heating rate in a tubular furnace in an air atmosphere to obtain the hollow multi-shell structure (ZnSSe (at) C) composite material. The preparation method is simple in steps and low in cost, and the prepared negative electrode material has high specific capacity, excellent cycle performance and rate capability when being used for the sodium-ion battery due to reasonable regulation and control of the material size, construction of the hollow multi-shell structure and doping of the selenium element, and has a wide application prospect in the field related to energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of next-generation energy materials technology, and in particular to a hollow multi-shell ZnSSe@C composite material, its preparation method, and its application. Background Technology

[0002] Against the backdrop of continuously growing global energy demand, the development of efficient and low-cost new energy storage technologies is urgently needed. Lithium-ion batteries (LIBs) are widely used in commercial electronic products due to their considerable energy density and excellent cycle life. However, the uneven natural distribution of lithium resources and safety concerns hinder the large-scale application of LIBs. Therefore, sodium-ion batteries (SIBs), with a similar mechanism, have once again come into focus due to their abundant resources, low cost, and good safety, becoming the most promising alternative. However, the radius of sodium ions is larger than that of lithium ions, meaning that most conventional electrode materials used in LIBs cannot be used in SIBs. Therefore, developing electrode materials with good electrochemical performance is a key technology for the development of SIBs.

[0003] Sodium-ion batteries consist of positive electrode materials, negative electrode materials, and electrolytes. Negative electrode materials can be classified according to their reaction mechanisms into intercalation-type negative electrode materials, alloy-type negative electrode materials, and conversion-type negative electrode materials. Among these, conversion-type negative electrode materials are mainly compounds composed of transition metals and oxygen, sulfur, selenium, and phosphorus. They have attracted widespread attention due to their advantages such as high theoretical specific capacity, good charge-discharge cycle stability, and low cost. Within conversion-type negative electrode materials, transition metal sulfides stand out from other materials due to their excellent electronic conductivity and multi-electron reaction mechanism.

[0004] Zinc sulfide has a high theoretical capacity (550mAh g). -1 Sodium ionomer (SO4) is an ideal anode material for sodium-ion batteries due to its environmental friendliness, abundant resources, diverse morphologies, and ease of manipulation. However, it still faces many challenges in practical applications, including large volume changes during electrochemical reversibility, relatively low conductivity, and slow kinetics. To address these issues, researchers have implemented a series of modifications to the anode material, such as carbon coating, heterostructures, and defect engineering.

[0005] Defect engineering in battery anode materials intentionally introduces or modulates defect structures to enhance electronic / ionic conductivity, increase active sites, and optimize interfacial reaction kinetics, significantly improving their electrochemical performance. Furthermore, rational structural design is also an effective way to improve electrochemical performance. Hollow multi-shell structures have internal cavities that can adapt to volume changes during repeated charge-discharge cycles. The multiple shells separate the internal space, preventing the accumulation of active materials during cycling and improving cycle stability by maintaining structural integrity. Simultaneously, nano-sized materials provide a larger specific surface area, increasing sodium ion adsorption and reaction interfaces, thereby improving reversible capacity. Therefore, rationally controlling dimensions and constructing hollow multi-shell structures is an effective strategy for improving battery energy density, cycle stability, and rate performance.

[0006] Based on this, this invention proposes the preparation of a hollow multi-shell ZnSSe@C composite material. By adjusting the size, structure, and composition, a sodium-ion battery anode material with high capacity, long cycle life, and high rate capability is obtained, providing a feasible approach and method for exploring novel energy storage electrode materials. In this invention, the size of the active material is controlled by a carbon source, a hollow multi-shell structure is built through high-temperature sintering, and selenium is doped into zinc sulfide. These multi-faceted synergistic controls comprehensively improve the material's capacity, rate capability, and cycle performance. Summary of the Invention

[0007] To address the aforementioned issues, this invention provides a hollow multi-shell ZnSSe@C composite material, its preparation method, and its applications. The method provided by this invention is simple, low-cost, and its dimensions are easily controllable. Furthermore, it exhibits superior electrochemical performance when used as a negative electrode material for sodium-ion batteries.

[0008] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing a hollow multi-shell ZnSSe@C composite material, comprising the following steps: 1) Ammonia, resorcinol, formaldehyde, deionized water and anhydrous ethanol were mixed and reacted in a water bath, followed by a hydrothermal reaction. The mixture was then centrifuged, washed and dried to obtain phenolic resin microspheres. 2) The phenolic resin microspheres obtained in step 1) are mixed with zinc acetate dihydrate and deionized water and then subjected to water bath deposition. The mixture is then washed and dried sequentially to obtain ZnO@RF. 3) The ZnO@RF obtained in step 2) is mixed with sulfur powder and selenium powder, and sintered at high temperature under a nitrogen atmosphere to obtain ZnSSe@C spherical composite material; 4) The ZnSSe@C spherical composite material described in step 3) is sintered at high temperature in an air atmosphere to obtain a hollow multi-shell ZnSSe@C composite material.

[0009] Preferably, the volume ratio of ammonia water, resorcinol, formaldehyde, deionized water, and anhydrous ethanol in step 1) is 0.3~0.9ml:0.3~0.6g:0.56ml:40ml:20ml.

[0010] Preferably, the conditions for the water bath reaction in step 1) include: a temperature of 30~40℃ and a time of 12~24h; The conditions for the hydrothermal reaction include: a temperature of 100°C and a time of 24 hours; The centrifugation conditions include: a rotation speed of 6000 rpm and a time of 5 min; Wash with alternating washes of anhydrous ethanol and deionized water; The drying conditions include a temperature of 60°C and a time of 12 hours.

[0011] Preferably, the mass ratio of the phenolic resin microspheres in step 2) to the mass of zinc acetate dihydrate and the volume of deionized water is 0.4g:10.4g:120ml.

[0012] Preferably, the conditions for water bath deposition in step 2) include: a temperature of 60°C and a time of 6 hours; Wash with alternating washes of anhydrous ethanol and deionized water; The drying conditions include a temperature of 60°C and a time of 12 hours.

[0013] Preferably, in step 3), the mass ratio of ZnO@RF to sulfur powder and selenium powder is 100:200~300:25~50; The conditions for high-temperature sintering include: heating to 600°C at a rate of 2°C / min and holding at that temperature for 2 hours.

[0014] Preferably, the conditions for high-temperature sintering in step 4) include: heating to 500°C at a heating rate of 1~3°C / min and holding for 2 hours.

[0015] The present invention also provides a hollow multi-shell ZnSSe@C composite material prepared by the preparation method described above.

[0016] This invention also provides the application of the hollow multi-shell ZnSSe@C composite material described in the above technical solution in the preparation of sodium-ion batteries.

[0017] Preferably, the components of the sodium-ion battery include the hollow multi-shell ZnSSe@C composite material, Ketjen black, and polydifluoroethylene; The hollow multi-shell structure of the ZnSSe@C composite material, Ketjen black, and polydifluoroethylene has a mass ratio of 7:2:1.

[0018] The beneficial effects of this invention are: (1) In electrode materials, the size and agglomeration of active materials have a significant impact on the electrochemical performance of batteries. This invention uses phenolic resin as a template to construct a hollow multi-shell structure. The size of the phenolic resin microspheres is controllable and they are uniformly dispersed, which solves the problem of uncontrollable size caused by previous methods of using sucrose, glucose, etc. as templates, and effectively improves the electrochemical performance.

[0019] (2) The present invention introduces vacancies and defects by doping selenium into zinc sulfide, thereby inducing additional active sites and increasing reversible capacity, improving electron mobility and thus enhancing conductivity and reaction kinetics, providing feasible ideas and methods for exploring new energy storage electrode materials.

[0020] (3) The hollow multi-shell structure of the ZnSSe@C composite material constructed in this invention can alleviate the volume expansion during the reaction process and enhance cycle stability. The multi-shell structure provides a larger specific surface area, increases the sodium ion adsorption and reaction interface, and improves capacity, making it particularly suitable for manufacturing sodium ion battery anodes. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the embodiments will be briefly described below.

[0022] Figure 1 Field emission scanning electron microscope (SEM) image of the hollow multi-shell ZnSSe@C composite material prepared in Example 1; Figure 2 The hollow multi-shell ZnSSe@C electrode material prepared in Example 1 was used as a negative electrode material for a sodium-ion battery at 2A g. -1 Cyclic performance diagram after 1000 cycles at current density. Detailed Implementation

[0023] This invention provides a method for preparing a hollow multi-shell ZnSSe@C composite material, comprising the following steps: 1) Ammonia, resorcinol, formaldehyde, deionized water and anhydrous ethanol were mixed and reacted in a water bath, followed by a hydrothermal reaction. The mixture was then centrifuged, washed and dried to obtain phenolic resin microspheres. 2) The phenolic resin microspheres obtained in step 1) are mixed with zinc acetate dihydrate and deionized water and then subjected to water bath deposition. The mixture is then washed and dried sequentially to obtain ZnO@RF. 3) The ZnO@RF obtained in step 2) is mixed with sulfur powder and selenium powder, and sintered at high temperature under a nitrogen atmosphere to obtain ZnSSe@C spherical composite material; 4) The ZnSSe@C spherical composite material described in step 3) is sintered at high temperature in an air atmosphere to obtain a hollow multi-shell ZnSSe@C composite material.

[0024] This invention involves mixing ammonia, resorcinol, formaldehyde, deionized water, and anhydrous ethanol, followed by a water bath reaction and a hydrothermal reaction. The mixture is then centrifuged, washed, and dried sequentially to obtain phenolic resin microspheres. In this invention, the particle size of the phenolic resin microspheres is preferably 200 nm to 1.2 µm. The preferred volume ratio of ammonia, resorcinol, formaldehyde, deionized water, and anhydrous ethanol is 0.3–0.9 ml: 0.3–0.6 g: 0.56 ml: 40 ml: 20 ml. The preferred conditions for the water bath reaction are a temperature of 30–40 °C and a time of 12–24 h. The preferred conditions for the hydrothermal reaction are a temperature of 100 °C and a time of 24 h. The preferred centrifugation conditions are a speed of 6000 rpm and a time of 5 min. This invention preferably uses alternating washing with anhydrous ethanol and deionized water. In this invention, the drying conditions preferably include a temperature of 60°C and a time of 12 hours.

[0025] In this invention, phenolic resin microspheres are mixed with zinc acetate dihydrate and deionized water, and then subjected to water bath deposition, followed by washing and drying to obtain ZnO@RF. In this invention, the preferred mass ratio of the phenolic resin microspheres to the zinc acetate dihydrate and the deionized water is 0.4 g:10.4 g:120 ml. The preferred conditions for the water bath deposition are a temperature of 60°C and a time of 6 hours. Anhydrous ethanol and deionized water are preferably used for washing. The preferred drying conditions are a temperature of 60°C and a time of 12 hours.

[0026] This invention involves mixing ZnO@RF with sulfur powder and selenium powder, and then sintering the mixture at high temperature under a nitrogen atmosphere to obtain a ZnSSe@C spherical composite material. In this invention, the preferred mass ratio of ZnO@RF to sulfur powder and selenium powder is 100:200~300:25~50. The preferred high-temperature sintering conditions include heating to 600℃ at a rate of 2℃ / min and holding at that temperature for 2 hours.

[0027] This invention involves sintering the ZnSSe@C spherical composite material at high temperature in an air atmosphere to obtain a hollow multi-shell ZnSSe@C composite material. In this invention, the preferred conditions for high-temperature sintering include: heating to 500°C at a rate of 1-3°C / min and holding at that temperature for 2 hours.

[0028] The present invention also provides a hollow multi-shell ZnSSe@C composite material prepared by the preparation method described above.

[0029] This invention also provides the application of the hollow multi-shell ZnSSe@C composite material described in the above-mentioned technical solution in the preparation of sodium-ion batteries. In this invention, the sodium-ion battery preferably comprises the hollow multi-shell ZnSSe@C composite material, Ketjen Black, and polydifluoroethylene (PVC). In this invention, the preferred mass ratio of the hollow multi-shell ZnSSe@C composite material, Ketjen Black, and PVC is 7:2:1. This invention does not have specific limitations on the source of the Ketjen Black and PVC; commercially available products commonly used in the preparation of sodium-ion batteries are acceptable.

[0030] To further illustrate the present invention, the following detailed description is provided in conjunction with embodiments, but these should not be construed as limiting the scope of protection of the present invention.

[0031] Example 1: A method for preparing a hollow multi-shell ZnSSe@C composite material, the steps of which are as follows: 1. Add 0.4 ml of ammonia, 0.4 g of resorcinol, and 0.56 ml of formaldehyde stepwise to a mixed solution of 40 ml of deionized water and 20 ml of anhydrous ethanol. Stir in a water bath at 40 °C for 12 h. Then transfer to a 100 ml polytetrafluoroethylene reactor and react at 100 °C for 24 h. Centrifuge and dry to obtain phenolic resin microspheres (RF) with a size of 200~400 nm. 2. Dissolve 10.4g of zinc acetate dihydrate in 120ml of deionized water. Then add 0.4g of RF and stir in a water bath at 60℃ for 6 hours to obtain ZnO@RF. 3. Mix 100mg ZnO@RF, 50mg selenium powder, and 200mg sulfur powder evenly in a tube furnace under nitrogen atmosphere and keep at 600℃ for 2h with a heating rate of 2℃ / min to obtain ZnSSe@C spherical composite material. 4. The ZnSSe@C spherical composite material was heated at 500℃ for 2 hours in an air atmosphere in a tube furnace with a heating rate of 1℃ / min to obtain a hollow multi-shell ZnSSe@C composite material.

[0032] The prepared ZnSSe@C battery anode material, Ketjen black, and polyvinyl difluoride (PVDF) were mixed in an N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 7:2:1. The mixture was stirred to obtain a uniform slurry, which was then coated onto a copper foil current collector and dried overnight in a vacuum oven at 120°C. After cooling to room temperature, the slices were removed, weighed, and equilibrated in a glove box for 8 hours before being assembled into a sodium-ion battery. The electrochemical performance of the battery was then tested.

[0033] Example 2: A method for preparing a hollow multi-shell ZnSSe@C composite material, the steps of which are as follows: 1. Add 0.4 ml of ammonia, 0.4 g of resorcinol, and 0.56 ml of formaldehyde stepwise to a mixed solution of 40 ml of deionized water and 20 ml of anhydrous ethanol. Stir in a water bath at 40 °C for 12 h. Then transfer to a 100 ml polytetrafluoroethylene reactor and react at 100 °C for 24 h. Centrifuge and dry to obtain phenolic resin microspheres (RF) with a size of 200~400 nm. 2. Dissolve 10.4g of zinc acetate dihydrate in 120ml of deionized water. Then add 0.4g of RF and stir in a water bath at 60℃ for 6 hours to obtain ZnO@RF. 3. Mix 100mg ZnO@RF, 25mg selenium powder, and 300mg sulfur powder evenly in a tube furnace under nitrogen atmosphere and keep at 600℃ for 2h with a heating rate of 2℃ / min to obtain ZnSSe@C spherical composite material. 4. The ZnSSe@C spherical composite material was heated at 500℃ for 2 hours in an air atmosphere in a tube furnace with a heating rate of 2℃ / min to obtain a hollow multi-shell ZnSSe@C composite material.

[0034] The prepared ZnSSe@C battery anode material, Ketjen black, and polyvinyl difluoride (PVDF) were mixed in an N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 7:2:1. The mixture was stirred to obtain a uniform slurry, which was then coated onto a copper foil current collector and dried overnight in a vacuum oven at 120°C. After cooling to room temperature, the slices were removed, weighed, and equilibrated in a glove box for 8 hours before being assembled into a sodium-ion battery. The electrochemical performance of the battery was then tested.

[0035] Example 3: A method for preparing a hollow multi-shell ZnSSe@C composite material, the steps of which are as follows: 1. Add 0.4 ml of ammonia, 0.4 g of resorcinol, and 0.56 ml of formaldehyde stepwise to a mixed solution of 40 ml of deionized water and 20 ml of anhydrous ethanol. Stir in a water bath at 40 °C for 12 h. Then transfer to a 100 ml polytetrafluoroethylene reactor and react at 100 °C for 24 h. Centrifuge and dry to obtain phenolic resin microspheres (RF) with a size of 200~400 nm. 2. Dissolve 10.4g of zinc acetate dihydrate in 120ml of deionized water. Then add 0.4g of RF and stir in a water bath at 60℃ for 6 hours to obtain ZnO@RF. 3. Mix 100mg ZnO@RF, 50mg selenium powder, and 200mg sulfur powder evenly in a tube furnace under nitrogen atmosphere at 600℃ for 2h, with a heating rate of 2℃ / min to obtain ZnSSe@C spherical composite material. 4. The ZnSSe@C spherical composite material was heated at 500℃ for 2 hours in an air atmosphere in a tube furnace with a heating rate of 3℃ / min to obtain a hollow multi-shell ZnSSe@C composite material.

[0036] The prepared ZnSSe@C battery anode material, Ketjen black, and polyvinyl difluoride (PVDF) were mixed in an N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 7:2:1. The mixture was stirred to obtain a uniform slurry, which was then coated onto a copper foil current collector and dried overnight in a vacuum oven at 120°C. After cooling to room temperature, the slices were removed, weighed, and equilibrated in a glove box for 8 hours before being assembled into a sodium-ion battery. The electrochemical performance of the battery was then tested.

[0037] Example 4: A method for preparing a hollow multi-shell ZnSSe@C composite material, the steps of which are as follows: 1. Add 0.3 ml of ammonia, 0.6 g of resorcinol, and 0.56 ml of formaldehyde stepwise to a mixed solution of 40 ml of deionized water and 20 ml of anhydrous ethanol. Stir in a water bath at 40 °C for 12 h. Then transfer to a 100 ml polytetrafluoroethylene reactor and react at 100 °C for 24 h. Centrifuge and dry to obtain phenolic resin microspheres (RF) with a size of 400~600 nm. 2. Dissolve 10.4g of zinc acetate dihydrate in 120ml of deionized water. Then add 0.4g of RF and stir in a water bath at 60℃ for 6 hours to obtain ZnO@RF. 3. Mix 100mg ZnO@RF, 25mg selenium powder, and 300mg sulfur powder evenly in a tube furnace under a nitrogen atmosphere and keep at 600℃ for 2h with a heating rate of 2℃ / min to obtain ZnSSe@C spherical composite material. 4. The ZnSSe@C spherical composite material was heated at 500℃ for 2 hours in an air atmosphere in a tube furnace with a heating rate of 1℃ / min to obtain a hollow multi-shell ZnSSe@C composite material.

[0038] The prepared ZnSSe@C battery anode material, Ketjen black, and polyvinyl difluoride (PVDF) were mixed in an N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 7:2:1. The mixture was stirred to obtain a uniform slurry, which was then coated onto a copper foil current collector and dried overnight in a vacuum oven at 120°C. After cooling to room temperature, the slices were removed, weighed, and equilibrated in a glove box for 8 hours before being assembled into a sodium-ion battery. The electrochemical performance of the battery was then tested.

[0039] Example 5: A method for preparing a hollow multi-shell ZnSSe@C composite material, comprising the following steps: 1. Add 0.3 ml of ammonia, 0.6 g of resorcinol, and 0.56 ml of formaldehyde stepwise to a mixed solution of 40 ml of deionized water and 20 ml of anhydrous ethanol. Stir in a water bath at 40 °C for 12 h. Then transfer to a 100 ml polytetrafluoroethylene reactor and react at 100 °C for 24 h. Centrifuge and dry to obtain phenolic resin microspheres (RF) with a size of 400~600 nm. 2. Dissolve 10.4g of zinc acetate dihydrate in 120ml of deionized water. Then add 0.4g of RF and stir in a water bath at 60℃ for 6 hours to obtain ZnO@RF. 3. Mix 100mg ZnO@RF, 50mg selenium powder, and 200mg sulfur powder evenly in a tube furnace under nitrogen atmosphere at 600℃ for 2h, with a heating rate of 2℃ / min to obtain ZnSSe@C spherical composite material. 4. The ZnSSe@C spherical composite material was heated at 500℃ for 2 hours in an air atmosphere in a tube furnace with a heating rate of 2℃ / min to obtain a hollow multi-shell ZnSSe@C composite material.

[0040] The prepared ZnSSe@C battery anode material, Ketjen black, and polyvinyl difluoride (PVDF) were mixed in an N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 7:2:1. The mixture was stirred to obtain a uniform slurry, which was then coated onto a copper foil current collector and dried overnight in a vacuum oven at 120°C. After cooling to room temperature, the slices were removed, weighed, and equilibrated in a glove box for 8 hours before being assembled into a sodium-ion battery. The electrochemical performance of the battery was then tested.

[0041] Example 6: A method for preparing a hollow multi-shell ZnSSe@C composite material, the steps of which are as follows: 1. Add 0.3 ml of ammonia, 0.6 g of resorcinol, and 0.56 ml of formaldehyde stepwise to a mixed solution of 40 ml of deionized water and 20 ml of anhydrous ethanol. Stir in a water bath at 40 °C for 12 h. Then transfer to a 100 ml polytetrafluoroethylene reactor and react at 100 °C for 24 h. Centrifuge and dry to obtain phenolic resin microspheres (RF) with a size of 400~600 nm. 2. Dissolve 10.4g of zinc acetate dihydrate in 120ml of deionized water. Then add 0.4g of RF and stir in a water bath at 60℃ for 6 hours to obtain ZnO@RF. 3. Mix 100mg ZnO@RF, 25mg selenium powder, and 300mg sulfur powder evenly in a tube furnace under a nitrogen atmosphere and keep at 600℃ for 2h with a heating rate of 2℃ / min to obtain ZnSSe@C spherical composite material. 4. The ZnSSe@C spherical composite material was heated at 500℃ for 2 hours in an air atmosphere in a tube furnace with a heating rate of 3℃ / min to obtain a hollow multi-shell ZnSSe@C composite material.

[0042] The prepared ZnSSe@C battery anode material, Ketjen black, and polyvinyl difluoride (PVDF) were mixed in an N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 7:2:1. The mixture was stirred to obtain a uniform slurry, which was then coated onto a copper foil current collector and dried overnight in a vacuum oven at 120°C. After cooling to room temperature, the slices were removed, weighed, and equilibrated in a glove box for 8 hours before being assembled into a sodium-ion battery. The electrochemical performance of the battery was then tested.

[0043] Example 7: A method for preparing a hollow multi-shell ZnSSe@C composite material, the steps of which are as follows: 1. Add 0.9 ml of ammonia, 0.3 g of resorcinol, and 0.56 ml of formaldehyde stepwise to a mixed solution of 40 ml of deionized water and 20 ml of anhydrous ethanol. Stir in a water bath at 40 °C for 12 h. Then transfer to a 100 ml polytetrafluoroethylene reactor and react at 100 °C for 24 h. Centrifuge and dry to obtain phenolic resin microspheres (RF) with a size of 600 nm to 1.2 μm. 2. Dissolve 10.4g of zinc acetate dihydrate in 120ml of deionized water. Then add 0.4g of RF and stir in a water bath at 60℃ for 6 hours to obtain ZnO@RF. 3. Mix 100mg ZnO@RF, 50mg selenium powder, and 200mg sulfur powder evenly in a tube furnace under nitrogen atmosphere and keep at 600℃ for 2h with a heating rate of 2℃ / min to obtain ZnSSe@C spherical composite material. 4. The ZnSSe@C spherical composite material was heated at 500℃ for 2 hours in an air atmosphere in a tube furnace with a heating rate of 1℃ / min to obtain a hollow multi-shell ZnSSe@C composite material.

[0044] The prepared ZnSSe@C battery anode material, Ketjen black, and polyvinyl difluoride (PVDF) were mixed in an N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 7:2:1. The mixture was stirred to obtain a uniform slurry, which was then coated onto a copper foil current collector and dried overnight in a vacuum oven at 120°C. After cooling to room temperature, the slices were removed, weighed, and equilibrated in a glove box for 8 hours before being assembled into a sodium-ion battery. The electrochemical performance of the battery was then tested.

[0045] Example 8: A method for preparing a hollow multi-shell ZnSSe@C composite material, the steps of which are as follows: 1. Add 0.9 ml of ammonia, 0.3 g of resorcinol, and 0.56 ml of formaldehyde stepwise to a mixed solution of 40 ml of deionized water and 20 ml of anhydrous ethanol. Stir in a water bath at 30 °C for 24 h. Then transfer to a 100 ml polytetrafluoroethylene reactor and react at 100 °C for 24 h. Centrifuge and dry to obtain phenolic resin microspheres (RF) with a size of 600 nm to 1.2 μm. 2. Dissolve 10.4g of zinc acetate dihydrate in 120ml of deionized water. Then add 0.4g of RF and stir in a water bath at 60℃ for 6 hours to obtain ZnO@RF. 3. Mix 100mg ZnO@RF, 25mg selenium powder, and 300mg sulfur powder evenly in a tube furnace under a nitrogen atmosphere and keep at 600℃ for 2h with a heating rate of 2℃ / min to obtain ZnSSe@C spherical composite material. 4. The ZnSSe@C spherical composite material was heated at 500℃ for 2 hours in an air atmosphere in a tube furnace with a heating rate of 2℃ / min to obtain a hollow multi-shell ZnSSe@C composite material.

[0046] The prepared ZnSSe@C battery anode material, Ketjen black, and polyvinyl difluoride (PVDF) were mixed in an N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 7:2:1. The mixture was stirred to obtain a uniform slurry, which was then coated onto a copper foil current collector and dried overnight in a vacuum oven at 120°C. After cooling to room temperature, the slices were removed, weighed, and equilibrated in a glove box for 8 hours before being assembled into a sodium-ion battery. The electrochemical performance of the battery was then tested.

[0047] Example 9: A method for preparing a hollow multi-shell ZnSSe@C composite material, the steps of which are as follows: 1. Add 0.9 ml of ammonia, 0.3 g of resorcinol, and 0.56 ml of formaldehyde stepwise to a mixed solution of 40 ml of deionized water and 20 ml of anhydrous ethanol. Stir in a water bath at 40 °C for 12 h. Then transfer to a 100 ml polytetrafluoroethylene reactor and react at 100 °C for 24 h. Centrifuge and dry to obtain phenolic resin microspheres (RF) with a size of 600 nm to 1.2 μm. 2. Dissolve 10.4g of zinc acetate dihydrate in 120ml of deionized water. Then add 0.4g of RF and stir in a water bath at 60℃ for 6 hours to obtain ZnO@RF. 3. Mix 100mg ZnO@RF, 50mg selenium powder, and 200mg sulfur powder evenly in a tube furnace under nitrogen atmosphere and keep at 600℃ for 2h with a heating rate of 2℃ / min to obtain ZnSSe@C spherical composite material. 4. The ZnSSe@C spherical composite material was heated at 500℃ for 2 hours in an air atmosphere in a tube furnace with a heating rate of 3℃ / min to obtain a hollow multi-shell ZnSSe@C composite material.

[0048] The prepared ZnSSe@C battery anode material, Ketjen black, and polyvinyl difluoride (PVDF) were mixed in an N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 7:2:1. The mixture was stirred to obtain a uniform slurry, which was then coated onto a copper foil current collector and dried overnight in a vacuum oven at 120°C. After cooling to room temperature, the slices were removed, weighed, and equilibrated in a glove box for 8 hours before being assembled into a sodium-ion battery. The electrochemical performance of the battery was then tested.

[0049] Test results: The nine hollow multi-shell ZnSSe@C battery anode materials prepared in Examples 1 (a), 2 (b), 3 (c), 4 (d), 5 (e), 6 (f), 7 (g), 8 (h), and 9 (i) were measured at 2A g. -1 Electrochemical performance at current density. Table 1 shows the characterization results of the hollow multi-shell ZnSSe@C battery anode materials prepared in Examples 1-9. As can be seen from the data in Table 1, the hollow multi-shell ZnSSe@C battery anode materials (a), (b), (c), (d), (e), (f), (g), (h), and (i) obtained using the preparation method described in this invention exhibit electrochemical performance at 2A g. -1 Under a certain number of cycles at a current density, it exhibits a capacity of 478 mAh g. -1 386mAh g -1 407mAh g -1 368mAh g -1 321mAh g -1 287mAh g -1 296mAh g -1 402mAh g -1 330mAh g -1 Excellent sodium storage performance.

[0050] Figure 1 This is a field emission scanning electron microscope (SEM) image of the hollow multi-shell ZnSSe@C composite material prepared in Example 1. Figure 1 The test results show that the hollow multi-shell ZnSSe@C composite material was successfully synthesized.

[0051] Figure 2 The hollow multi-shell ZnSSe@C electrode material prepared in Example 1 was used as a negative electrode material for a sodium-ion battery at 2A g. -1 Cyclic performance diagram after 1000 cycles at current density.

[0052] Table 1. Characterization results of hollow multi-shell ZnSSe@C battery anode materials

[0053] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a hollow multi-shell ZnSSe@C composite material, characterized in that, Includes the following steps: 1) Ammonia, resorcinol, formaldehyde, deionized water and anhydrous ethanol were mixed and reacted in a water bath, followed by a hydrothermal reaction. The mixture was then centrifuged, washed and dried to obtain phenolic resin microspheres. 2) The phenolic resin microspheres obtained in step 1) are mixed with zinc acetate dihydrate and deionized water and then deposited in a water bath. The mixture is then washed and dried to obtain ZnO@RF. 3) The ZnO@RF obtained in step 2) is mixed with sulfur powder and selenium powder, and sintered at high temperature under a nitrogen atmosphere to obtain ZnSSe@C spherical composite material; 4) The ZnSSe@C spherical composite material described in step 3) is sintered at high temperature in an air atmosphere to obtain a hollow multi-shell ZnSSe@C composite material.

2. The preparation method according to claim 1, characterized in that, In step 1), the volume ratio of ammonia, resorcinol, formaldehyde, deionized water, and anhydrous ethanol is 0.3~0.9ml:0.3~0.6g:0.56ml:40ml:20ml.

3. The preparation method according to claim 1, characterized in that, The conditions for the water bath reaction in step 1) include: a temperature of 30~40℃ and a time of 12~24h; The conditions for the hydrothermal reaction include: a temperature of 100°C and a time of 24 hours; The centrifugation conditions include: a rotation speed of 6000 rpm and a time of 5 min; Wash with alternating washes of anhydrous ethanol and deionized water; The drying conditions include a temperature of 60°C and a time of 12 hours.

4. The preparation method according to claim 1, characterized in that, Step 2) The mass ratio of the phenolic resin microspheres to the mass of zinc acetate dihydrate and the volume of deionized water is 0.4g:10.4g:120ml.

5. The preparation method according to claim 1, characterized in that, Step 2) The conditions for water bath deposition include: a temperature of 60°C and a time of 6 hours; Wash with alternating washes of anhydrous ethanol and deionized water; The drying conditions include a temperature of 60°C and a time of 12 hours.

6. The preparation method according to claim 1, characterized in that, Step 3) The mass ratio of ZnO@RF to sulfur powder and selenium powder is 100:200~300:25~50; The conditions for high-temperature sintering include: heating to 600°C at a rate of 2°C / min and holding at that temperature for 2 hours.

7. The preparation method according to claim 1, characterized in that, Step 4) The conditions for high-temperature sintering include: heating to 500℃ at a heating rate of 1~3℃ / min and holding for 2 hours.

8. A hollow multi-shell ZnSSe@C composite material prepared by the preparation method according to any one of claims 1 to 7.

9. The application of the hollow multi-shell ZnSSe@C composite material of claim 8 in the preparation of sodium-ion batteries.

10. The application according to claim 9, characterized in that, The components of the sodium-ion battery include the hollow multi-shell ZnSSe@C composite material, Ketjen black, and polydifluoroethylene; The hollow multi-shell structure of the ZnSSe@C composite material, Ketjen black, and polydifluoroethylene has a mass ratio of 7:2:1.

Citation Information

Patent Citations

  • Lithium ion battery anode material and preparation method thereof

    CN109768265A

  • Aqueous zinc-sulfur battery positive electrode material and preparation method thereof

    CN117457842A

  • Metal sulfide / selenide material with hollow porous rod-like structure as well as preparation method and application of metal sulfide / selenide material

    CN118352497A

  • Stock related information providing platform server and system including the same

    KR102349977B1

  • Carbon encapsulated sulfur-metal oxide composite, methods of preparation, and uses thereof

    US20190312263A1